Evaluating South Africa’s utilisation of sustained export potential in sub-Saharan Africa - Gabriel Mhonyera; Ermie Steenkamp; Marianne Matthee (South African Journal of Economic and Management Sciences, 2018)
Background: Regional trade could be a powerful engine of economic growth and sustainable job creation. However, South Africa’s exports to sub-Saharan Africa (SSA) are typically smaller and more short-lived than its exports to its traditional markets. This is despite South African policymakers considering trade with SSA to be a priority.